Molecular epidemiology and antimicrobial resistance of Clostridium difficile in a national geriatric hospital in Costa Rica - Jiménez Solís, Andrea (2018)
Background: the epidemiology of Clostridium difficile infections (CDI) is changing rapidly worldwide; knowledge on the genotypes of C. difficile circulating in specialized geriatric hospitals and their resistance to antibiotics is scarce or non-existent. Methods: prospective study of the molecular epidemiology of CDI, conducted in a national geriatric hospital in Costa Rica for a period of 11 months. Results: the study patients exhibited a diverse range of comorbidities, but none were associated with CDI. Polyclonality, including three new ribotypes, and a high level of resistance to antibiotics were determined by analysing the 32 isolates obtained in these cases. Despite the diversity in strains observed, the most frequent types were NAP6/RT002 and NAP2/RT001. NAP9/RT017 was associated with community acquisition. Nineteen types of antimicrobials were used before the onset of diarrhoea in the patients; no particular genotype was associated with the onset of infection or severity. Conclusion: based on the abundance of strain types observed and their resistance to antibiotics in this geriatric hospital, these results contribute to a better overall understanding of the epidemiology of CDI worldwide, and to surveillance programmes targeting geriatric populations.